(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: To formulate and evaluate controlled release herbal mosquito repellent gel containing encapsulated essential oils (EO) obtained from natural sources indigenous to North East India. Material & Methods: Essential oils were extracted from the fruits of Zanthoxylum acanthopodium (ZA) and Litsea cubeba (LC). The essentials oils were analysed using Gas chromatography and Mass spectrometry. Essential oils loaded Chitosan-Sodium lauryl sulphate (Chitosan-SLS) microparticles were prepared using ionic cross-linking method. Essential oils loaded microparticles were characterized using Fourier transformed infrared spectroscopy, Differential scanning calorimetry, Particle size and Encapsulation efficiency determination. Essential oils containing microparticles were loaded into a gel base containing Carbopol 934 and Lutrol F 127. Formulated gels were characterized by organoleptic characteristics, homogeneity test, pH determination, Viscosity determination, In vitro membrane permeation and Acute dermal irritation study. Mosquito repellent study was carried out for the gels using non-blood-fed females Aedes aegypti mosquitoes. Results & Discussion: The percentage yield of essential oils from the fruits of Zanthoxylum acanthopodium and Litsea cubeba were 0.8647 % w/w and 2.485 % w/w respectively. Encapsulation efficiencies of ZA EO loaded Chitosan-SLS microparticles and LC EO loaded chitosan-SLS microparticles particles were 97.16 % w/w and 96.64 % w/w respectively. Organoleptic properties of EO containing chitosan-SLS microparticles loaded gels were white in colour, having characteristic odour, homogenous and washable. pH of the gels were found within the range of 5.35 to 5.85. The formulated gel containing 3 % w/w essential oil in the encapsulated form (G3) demonstrated 21.49 % w/w permeation of essential oil in the study of in vitro membrane permeation. Maximum mosquito repellent activity was observed with G3 gel. Complete protection time for G3 gel was 2 h against Aedes aegypti. Protection time of G3 gel was observed up to 3 h. Acute dermal irritation study confirmed that there was no irritation effect due to the gels. Retained sample stability testing demonstrated that there was no significant change in gels over three months. Conclusion: The study resulted in successful development of a novel herbal controlled release mosquito repellent gel using essential oils from North East India.